PENGARUH BANTUAN TUNAI PENDIDIKAN DAN PROGRAM PEMBINAAN BAGI PENINGKATAN SUMBER DAYA MANUSIA PADA PROGRAM “ OEMAH SINAU ” LAZNAS AL-IRSYAD AL-ISLAMIYYAH PURWOKERTO - Fitria Dwi Larasfeni (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Human Resources refer to all potential skills, knowledge and abilities possessed by individuals in an organization and society. Philanthropic institutions play a role in efforts to improve the quality of human resources with the existence of the LAZNAS Al-Irsyad Purwokerto Institution. The institution has a program in collecting and utilizing Zakat, Infak and Sedekah funds, especially for the welfare of the people.This study aims to measure the level of success of institutions in improving the quality of human resources for OTA and BUY LAZNAS Al-Irsyad Purwokerto scholarship recipients. Based on these objectives, this study is a type of quantitative research. The sample taken is a saturated sample, where the researcher will take the entire population of 37 respondents who received the Foster Parents (OTA) and Orphan Scholarships (BUY) at LAZNAS Al-Irsyad Purwokerto. Spearman rank correlation analysis gives the results that partial cash assistance for education has a positive effect on the quality of human resources, this is because the sig. value is 0.002 <0.05. While the partial coaching program cannot affect the quality of human resources in the distribution of zakat and infaq funds in the OTA and BUY LAZNAS Al-Irsyad Purwokerto scholarship programs because the sig. value is 0.205> 0.05. The results of the Kendal W Concordance that the Test Statistics table shows a correlation of 0.967 or shows a very strong correlation between educational cash assistance and coaching programs on the quality of human resources. The Asymp.Sig. Value, ≤ 0.05 then the test decision is H0 is rejected, so it can be concluded that there is a significant relationship between educational cash assistance and coaching programs with the quality of human resources of OTA and BUY LAZNAS Al-Irsyad Purwokerto scholarship recipients.